NANOSTRUCTURAL PROCESSES OF MELTING AND MOULDING OF HYPOEUTECTIC SILUMIN - V. Yu. Stetsenko (Литьë и металлургия)
It is shown that melting and molding of hypoeutectic silumin are difficult physical and chemical nanostructural processes. In them the major role is played by the centers of crystallization of primary dendrites of aluminum, aluminum nanocrystals, the dissolved and adsorbed hydrogen. The role of the modifying crystals of an intermetallid of TiAl3 is reduced to absorption of the dissolved hydrogen and an intensification of process of a koalestsention of nanocrystals of aluminum in the centers of crystallization of primary dendrites of aluminum.